PENDEKATAN KONSELING MULTIKULTURAL TERHADAP PERSEPSI MASYARAKAT TENTANG BISSU DI SULAWESI SELATAN - Nurfadillah; Rifki Ahmad Fahrezi; Abdul Hakim; Samsinar Syarifuddin (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2026)
The presence of bissu in Bugis society in South Sulawesi forms part of a cultural heritage that serves social, cultural, symbolic and spiritual functions. This study aims to analyse public perceptions of bissu and to understand this phenomenon through the lens of multicultural counselling. This issue is important because the phenomenon of bissu is not only related to culture and religion but also concerns the formation of social perceptions within a multicultural society. The research employs a qualitative approach with a social phenomenological perspective. The data were collected through in-depth interviews, observation and documentation, and were subsequently analysed through the stages of restatement, description and interpretation. The research findings indicate that public perceptions of the bissu are shaped by the interplay between culture, religion, social experiences and changing values within society. The findings also suggest that a multicultural counselling approach, through cultural sensitivity, contextual understanding and reflective confrontation techniques, can help to reduce stereotypes, foster critical awareness and promote a more balanced understanding of cultural diversity. This study emphasises the importance of a multicultural counselling approach within Islamic Guidance and Counselling as a space for dialogue and social reflection, aimed at fostering more inclusive relationships within a diverse society.   Keywords: bissu, multicultural counselling, Bugis culture.